Mapping Contours of Reconciliation and Peace Process in Afghanistan: Policy Options for Pakistan - baneen, ummul; Mirza, Muhammad Nadeem; Abbas, Hussain (Journal of Peace, Development and Communication, 2020)
Afghan war has long been considered as a strategic failure, as the US could neither bring an end to the violence, nor ensure complete territorial control. Deteriorating security situation has also endangered stability of adjoining states. With the failure of military means to resolve Afghan crisis, the need for a political solution gained momentum resulting in the US-Taliban agreement in early 2020. This study traces out why, despite various rounds of talks and initiatives of reconciliation and peace process, the successful stability could not be achieved in Afghanistan. The study concluded that all the stake-holders continued to pursue unrealistic objectives, resulting in failure of the previous efforts of peace talks. The United States and Taliban, now, have been successful into signing the deal because both parties decided to not pursue optimal options – Taliban compromised to start itra-Afghan negotiations and fight againt Islamic State of Khorasan Province (ISKP) and Al-Qaeda, and the United States decided to gradually withdraw troops and remove sanctions it had imposed on Taliban. Other parties, such as Afghan government, also have to sacrifice a part of their interest in order to achieve the greater good of having a stable and peaceful Afghanistan. Key Words: Reconciliation, Peace Process, Afghanistan, Taliban, United States, Pakistan, Clashing interest.